CONVERGENCE OF CONSUMER PROTECTION, INVESTMENT LAW, AND CYBERSECURITY: An in-Depth Analysis of Three-Way Legal Intersections in Investment Apps - Rufinus Hotmaulana Hutauruk; Lu Sudirman; Hari Sutra Disemadi; David Tan (Jurisdictie: Jurnal Hukum dan Syariah, 2023)
Investment apps have become an important part of the investment culture throughout the world and have helped democratize investment opportunities for many people. The utilization of investment apps in Indonesia has opened many doors for Indonesians to invest their wealth and obtain many different kinds of assets, posing cybersecurity risks that threaten the interests of their users. This study aims to analyze and provide literature for possible future legislation that affects the utilization of investment apps. Using the normative legal research method, this study analyzes the intersection of investment law and consumer protection law in Indonesia in the context of the utilization of investment apps. Through the statutory approach, this study finds that the normative restrictions within the respective laws make it difficult to properly define legal liability for many kinds of problems that can arise from cybersecurity risks in the context of the utilization of investment apps. The findings of this article serve as a contribution to the constantly expanding literature for Indonesian legal development, specifically on the quest to adapt to the changes brought about by the latest technologies.Aplikasi investasi telah menjadi bagian penting dari budaya investasi di seluruh dunia dan telah membantu mendemokratisasi peluang investasi bagi banyak orang. Penggunaan aplikasi investasi di Indonesia telah membuka banyak pintu bagi masyarakat Indonesia untuk menginvestasikan kekayaan mereka dan mendapatkan berbagai jenis aset, yang menimbulkan risiko keamanan siber yang mengancam kepentingan penggunanya. Penelitian ini bertujuan untuk menganalisis dan menyediakan literatur untuk kemungkinan legislasi di masa depan yang mempengaruhi pemanfaatan aplikasi investasi. Dengan menggunakan metode penelitian hukum normatif, penelitian ini menganalisis persinggungan antara hukum investasi dan hukum perlindungan konsumen di Indonesia dalam konteks pemanfaatan aplikasi investasi. Melalui pendekatan perundang-undangan, penelitian ini menemukan bahwa pembatasan normatif dalam masing-masing undang-undang menyulitkan untuk mendefinisikan pertanggungjawaban hukum secara tepat untuk berbagai jenis masalah yang dapat timbul dari risiko keamanan siber dalam konteks penggunaan aplikasi investasi. Temuan dari artikel ini berfungsi sebagai kontribusi terhadap literatur yang terus berkembang untuk pengembangan hukum di Indonesia, khususnya dalam upaya untuk beradaptasi dengan perubahan yang dibawa oleh teknologi terbaru.